Faktor-faktor yang mempengaruhi deposito mudharabah pada bank syariah di Indonesia - Nila Juniarty; Mustika Noor Mifrahi; Achmad Tohirin (Faculty of Economics, Universitas Islam Indonesia, 2017)
Mudharabah Deposit is one of Islamic banking products, which is the biggest contributor to sharia banking compared to other collecting products. In addition, according to Bank Indonesia's report, the number of Islamic banking deposits each year has increased significantly. Therefore, in this study, the authors want to know the factors that are expected to affect the number of mudharabah deposits. There are 6 factors that are expected to affect the number of deposits, namely the profit-sharing rate, the interest rate, the promotion rate, the inflation rate, the FDR, and the number of offices. The authors use a weighted average in terms of rate of profit sharing and interest rate and data processing using multiple linear regression. The results of these regression calculations, simultaneously show positive and significant results for all variables. This value resulted from the four regression has a value of sig-F 0.000 is smaller than 10% significance. Partially, profit sharing, promotion cost and number of offices show significant and positive effect on total mudharabah deposit, while interest rate, inflation and FDR show no effect on mudharabah deposit amount.